Defaults and donations: Evidence from a field experiment - Steffen Altmann; Armin Falk; Paul Heidhues; Rajshri Jayaraman; Marrit Teirlinck (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We study how defaults affect charitable donations. In a field experiment that was conducted on a large online platform for charitable giving, we exogenously vary the default options in the donation form in two distinct choice dimensions. The first pertains to the primary donation decision, namely, how much to contribute to the charitable cause. The second relates to a "codonation" decision of how much to contribute to supporting the online platform itself. We find a strong impact of defaults on individual behavior: in each of our treatments, the modal positive contributions in both choice dimensions invariably correspond to the specified default amounts. Defaults, nevertheless, have no significant effects on average donation levels. This is because defaults in the donation domain induce some people to donate more and others to donate less. In contrast, higher defaults in the secondary choice dimension unambiguously induce higher average contributions to the online platform. We complement our experimental results by setting up and estimating a structural model that explores whether personalizing defaults based on individuals' donation histories can help the online platform to increase donation revenues.
Keywords: D03; D01; D64; C93; 330; Default Options; Online Platforms; Charitable Giving; Field Experiment